Management of trauma-induced discoloration in non-vital teeth using walking bleach technique: A case series - Gehlot, Paras Mull; Ghosh, Susmita; Shafiq, Shaima Misbah; Mariswamy, Annapoorna Ballagere (Journal of Orofacial Research, 2024)
An aesthetic smile is important since it influences a person’s psychosocial well-being and shapes the image of their aesthetic self. Non-vital tooth discoloration can be caused by several factors, the most frequent, however, are dental trauma and residual sealing materials in the pulp chamber following root canal treatment. Internal bleaching (Walking bleach or Thermocatalytic) is a minimally invasive alternative to veneers or crowns. This case series presents the management of trauma-induced discoloration in anterior teeth using the walking bleach technique. Patients reported with a chief complaint of discolored front teeth and their history revealed dental trauma. After the clinical and radiographic examination, endodontic therapy was performed. After recording the shade, the walking bleach technique was performed and the patients were recalled subsequently at weekly intervals, depending on the severity of discoloration. Further bleaching appointments were scheduled if needed. After obtaining a satisfactory improvement in the shade, a definite restoration was done. Conclusion: Proper case selection and patient education can lead to satisfactory outcomes. The walking-bleach technique is recommended as a safe alternative for treating discolored non-vital teeth.